A parametric study to numerically analyze the formation damage effect. Issue 2 (March 2020) - Davarpanah, Afshin; Mirshekari, Behnam; Razmjoo, Armin
Spontaneous countercurrent imbibition is one of the essential parameters in the study of formation damage effect in hydrocarbon reservoirs when the drilling fluid is contacted with the drilled formation. Formation damage is considered as one of the harmful phenomena which would seriously affect the efficiency of drilling performances. In this paper, a numerical model was proposed to analyze the main parameters which have profoundly impacted the formation damage. Based on the following parameters of porosity, permeability, water saturation, oil viscosity, pressure drop, contact time, and capillary pressure which were performed in the proposed model, the dominant influence of each parameter was evaluated in more detail. Regarding the high expenditures of scanning electron microscopy and CT scan in petroleum industries, the proposed analytical model would be beneficial instead of spending vast expenditures of experimental evaluation. Subsequently, to provide the accuracy of the model, a set of experimental CT scan data were used to validate the proposed model, and according to the results of this study, it is evident that the proposed model results are in a good agreement with the laboratory data.